Land policies: Actions to make up for lost times - Areas for partnering? - Köhlin, Gunnar (2013)
"Partnering for Impact: IFPRI-European Research Collaboration for Improved Food and Nutrition Security" presentation by Gunnar Köhlin, Director, Environment for Development, University of Gothenburg, on 25 November 2013 in Brussels, Belgium.